Association of Different Formulation with Oral Contraceptive Agents in Lipid and Carbohydrates Metabolism in Women: Oral Contraceptive Agents in Lipid and Carbohydrates Metabolism in Women - Hussain, Syeda Masooma; Khan, Sikandar Ali; Noor, Somaya; Fida, Najma; Bukhari, Syed Muhammad Sajid Ali; Zeb, Jahangir (Pakistan Journal of Health Sciences, 2025)
Oral contraceptives impact lipid and carbohydrate metabolism differently based on formulation. Objectives: To assess the association between Ethinylestradiol-Levonorgestrel, Ethinylestradiol-Norgestimate, and Progestin-Only contraceptives and key metabolic markers, including lipid profile and carbohydrate metabolism, in women using these formulations. Methods: A cross-sectional study recruited women aged 18–45 using one of these contraceptives for at least 6 months. Exclusion criteria included metabolic disorders, cardiovascular disease, and recent medication use affecting metabolism. Demographic and health data (BMI, blood pressure, waist-to-hip ratio) were collected. Metabolic markers—including cholesterol, LDL, HDL, triglycerides, Apolipoproteins A1/B, fasting glucose, fasting insulin, HOMA-IR, OGTT, and HbA1c were measured. Statistical tests included One-Way ANOVA, Kruskal-Wallis, and Tukey’s post-hoc (p<0.05). Results: Significant metabolic differences were observed. Ethinylestradiol-Levonorgestrel users had higher total cholesterol (p=0.002) and increased insulin resistance (HOMA-IR, p=0.019), suggesting a potential long-term cardiovascular risk. Ethinylestradiol-Norgestimate users exhibited higher Apo-lipoprotein A1 levels (p=0.005), indicating a possible cardio-protective effect in reducing atherosclerosis risk. HOMA-IR was also higher in Progestin-Only users compared to Ethinylestradiol-Norgestimate (p=0.006). No significant differences were found in fasting glucose or HbA1c. Conclusions: It was concluded that Ethinylestradiol-Norgestimate may have a more favourable metabolic profile, with lower cholesterol and insulin resistance. Tailored contraceptive selection could reduce metabolic risks, particularly in women with cardiovascular concerns. Further research is needed to assess long-term effects. However, the exclusion of women with pre-existing metabolic disorders limits the generalizability of these findings. Future studies should include these subgroups to provide a broader understanding of metabolic responses to oral contraceptives.